Social media livestreaming design for disruption? - Artwick, Claudette Guzan (Disruptions: studies in digital journalism, 2019)
"Addresses a host of emerging issues concerning social media livestreaming, exploring this technology as a disruption and its potential to shape journalism practice and influence society. Live visual images increasingly inundate our digital screens. While once restricted to broadcast news organizations, "going live" is becoming ubiquitous, fueled by smartphones and social networks. As livestreams and eyewitness video permeate our social media feeds, a wide range of possibilities for journalism and society are unfolding. Using international case studies, interviews with journalists, and survey research with citizens, this book explores major themesincluding livestreaming's implications for journalism practice and news content production; citizen activism and participation in democracy; ethical, legal, safety and privacy considerations; and the role of livestreaming in shaping public perception"--Publisher